DETERMINATION OF VANILLIN IN VANILLA (Vanilla planifolia Andrews) FROM LAMPUNG INDONESIA BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Siti Sujalmi; Suharso Suharso; R Supriyanto; Buchari Buchari (Indonesian Journal of Chemistry, 2005)
This paper describes a reverse-phase high performance liquid chromatographic (HPLC) method for the separation, identification and quantification of vanillin in ethanolic extracts of cured vanilla. The fresh green beans were cured by three methods: scalding in hot water, drying in the oven, and drying in the sun. Two treatments for the cured beans before extraction, there were cutting cured vanilla about 2.5 cm and not cutting. The extraction was with Soxhletation and percolation method in 99.9 % ethanol. The vanillin was separated on C18 column using a mobile phase gradient of methanol  - acidified water (10-90), detection at 280 nm. The HPLC technique allows a more accurate means of determining the vanillin  content of vanilla than  the spectrophotometric method.